A taxonomic revision of Atelopus pachydermus, and description of two new (extinct?) species of Atelopus from Ecuador (Anura: Bufonidae). - Coloma, L.A. (2007)
Atelopus pachydermus is redescribed on the basis of the retraced holotype and recently collected specimens. Comparisons with the holotype confirmed that this species occurs neither in Pacific Colombia, nor in the northeastern Cordillera of Ecuador, as proposed by previous authors. It occurs in the northwestern Andes of Peru and adjacent Ecuador. Populations from the Cordillera Oriental in northern Ecuador (some of them previously allocated to A. pachydermus) are described as a new species, which is distinguished from other Atelopus by size, coloration, and by having white digital pads that contrast with adjacent black phalanges. In addition, a population of Atelopus from the Andes of southwestern Ecuador, previously included in the Atelopus bomolochos complex, and having an aqua blue iris is described as a new species. We include osteological data of both new species. Predictions of numbers of species of Atelopus to be discovered and described, as well as of numbers for Ecuadorian amphibian diversity, indicates that these faunas are yet largely undescribed. Because recent records of A. pachydermus and the two new species are lacking despite search efforts, we assume that they are possibly extinct, similar to many other Andean Atelopus. Thus, we categorize these species either as possibly extinct or, applying IUCN Red List criteria, as Critically Endangered. Current evidence suggests that amphibian extinctions in the Ecuadorian and Peruvian Andes have been more drastic than previously recognized.